Polish literature and the Konzentrationslager. The beginning - Morawiec, Arkadiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
In the article the author discusses the beginnings of Polish camp literature, more precisely: literature referring to the Nazi German concentration camps. For decades it was assumed that the earliest Polish texts of that type were published in 1945. It appears that the first works – reports and memoirs – were published before the outbreak of WWII. In this article, the author discusses them in the historical and historical-literary contexts (mainly in the context of German writings).